2008
DOI: 10.1158/1055-9965.epi-07-2812
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aryl Hydrocarbon Receptor Gene Polymorphisms and Urinary 1-Hydroxypyrene in Polycyclic Aromatic Hydrocarbon–Exposed Workers

Abstract: Polycyclic aromatic hydrocarbons (PAH) in coke oven emissions could cause lung cancer in human. Individual's genotype of the metabolic enzymes and early biological changes were known to be associated with the susceptibility of cancer development. Knowledge of metabolic gene polymorphisms, which affect on the urinary 1-hydroxypyrene (1-OHP), could benefit us in understanding the interindividual difference in the mechanism of PAH-induced carcinogenesis. In this study, we investigated the association of aryl hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…Data from the present study also showed that levels of urinary 1-OHP differed significantly according to exposure to PAHs among coke oven workers. This is in consistent with occupational studies on PAH-exposed persons, including coke oven workers (Ovrebo et al, 1998;van Delft et al, 2001;Bin et al, 2008). The results were higher than the investigations performed in West European coke oven workers which revealed lower levels of 1-OHP, not exceeding in average the concentration of 2 μmol/mol creatinine (Ovrebo et al, 1998;van Delft et al, 2001;Marczynski et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Data from the present study also showed that levels of urinary 1-OHP differed significantly according to exposure to PAHs among coke oven workers. This is in consistent with occupational studies on PAH-exposed persons, including coke oven workers (Ovrebo et al, 1998;van Delft et al, 2001;Bin et al, 2008). The results were higher than the investigations performed in West European coke oven workers which revealed lower levels of 1-OHP, not exceeding in average the concentration of 2 μmol/mol creatinine (Ovrebo et al, 1998;van Delft et al, 2001;Marczynski et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Epidemiologic studies indicate that occupational exposure to PAH was well correlated with the levels of PAH metabolites such as 1-OHP in urine. 1-OHP is a major metabolite of pyrene that has been shown to be a good marker for total PAH exposure and is thought to reflect PAH activation (Nerurkar et al, 2000;Castaño-Vinyals et al, 2004;Bin et al, 2008). Data from the present study also showed that levels of urinary 1-OHP differed significantly according to exposure to PAHs among coke oven workers.…”
Section: Discussionsupporting
confidence: 57%
“…Previous literature [13] and our study have proved a fact that the higher levels of AHR and AHRR expression in RA patients than that in controls. Currently, a large number of studies have discussed the association of the genetic polymorphism of AHR and related diseases such as male infertility, [14,15] lung cancer, [16,17] non-Hodgkin lymphoma, [18] urinary 1-hydroxypyrene in polycyclic aromatic hydrocarbon-exposed workers, [19] and vitiligo. [20] In addition, we selected the rs2066853 in intron10 for it widely being studied in a list of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Less acute (between a few hours to days) and chronic indirect effects may occur via oxidative stress pathways, which can lead to autonomic cardiac imbalance as an increase in sympathetic and a reduction in parasympathetic tone 22. PAHs may affect autonomic cardiac dysfunction indirectly by promoting reactive oxygen species by inducing xenobiotic metabolising enzymes such as the cytochrome P450 (CYP) family that plays a central role in the onset, progression and prognosis of CVDs31 through an arylhydrocarbon receptor (AhR)-dependent manner 32 33. The CYP families have been identified in cardiovascular tissue including heart, endothelial cells and smooth muscle of blood vessels 31.…”
Section: Discussionmentioning
confidence: 99%